Inovation of Vocational High School 1 Kalibawang, Wonosobo in the economics recovery of pandemic covid-19 - Hidayat, Aftrino Ridlo (Prosiding University Research Colloquium, 2021)
The covid-19 pandemic erupted throughout the district of Wonosobo. Economic sector is the one of sector that gets special attention after the health care. Wonosobo’s economy is in crisis situation, affected from both, inside and outside the region. This big problem should receive immediate attention to avoid further deterioration. Through qualitative descriptive studies, the paper was aiming for reveal the natural resources at Wonosobo that can be used for economic recovery after the covid-19 pandemic. Wonosobo regency which has a wealth of natural resources and people wo work as a farm, so the economic recovery strategies can rely on the agricultural sector and the people’s business sectors on worthy commodities. In terms of economic recovery in this difficult situation not only the responsibility of the country. The program from Vocational High School One Kalibawang Wonosobo to build a villages is one of the economic recovery innovation. This innovation is a form of cooperation between SMK N 1 Kalibawang and the village community.